Hypofractionated stereotactic photon radiotherapy of choroidal melanoma: 20-year experience. (1st February 2021) - Eibenberger, Katharina; Dunavoelgyi, Roman; Gleiss, Andreas; Sedova, Aleksandra; Georg, Dietmar; Poetter, Richard; Dieckmann, Karin; Zehetmayer, Martin
Abstract: Background: To evaluate the long-term results after hypofractionated stereotactic photon radiotherapy (SRT) in patients with choroidal melanoma treated between 1997 and 2016. Material and methods: A total of 335 patients (183 male and 152 female) with choroidal melanoma unsuitable for ruthenium-106 brachytherapy or local resection were treated with linear accelerator-based SRT at the Medical University of Vienna. All patients received five fractions with either 10, 12 or 14 Gy per fraction. A complete ophthalmic examination including visual acuity and measurement of the tumor base and height using standardized A- and B-scan ultrasonography was performed every 3 months in the first 2 years, every 6 months until 5 years and yearly thereafter. Early and late adverse side effects were assessed at every follow-up visit. Results: The median overall follow-up was 78.6 months (39.1 to 113.7 months). Local tumor control was 95.4% after 10 and 12 years, respectively. Fifty-four patients developed metastatic disease, and 31 died during the follow-up. Mean visual acuity decreased from 0.55 Snellen at baseline to 0.05 Snellen at the last individual follow-up. Ischemic retinopathy (192/335cases) and optic neuropathy (174/335cases) were the most common radiogenic side effects, followed by radiogenic cataract ( n  = 127), neovascular glaucoma ( n  = 71) and corneal epithelium defects ( n  = 49). Enucleation was performed in 54 patients mostly due to neovascular glaucoma ( n  = 41) or tumor recurrence ( n  = 10) during the study period. The eye retention rate was 79.7% after 10 and 12 years. Conclusion: Hypofractionated stereotactic photon radiotherapy showed a high rate of local tumor control for choroidal melanoma and an acceptable rate of radiogenic side effects.